Returns to Education in Sri Lanka : A Pseudo-Panel Approach - Himaz, Rozana; Aturupane, Harsha (Taylor and Francis, 2015)
This study employs a pseudo-panel approach to estimate the returns to education among income earners in Sri Lanka. Pseudo-panel data are constructed from nine repeated cross sections of Sri Lanka's Labor Force Survey data from 1997 to 2008, for workers born during 1953–1974. The results show that for males, one extra year of education increases monthly earnings by about 5% using the pseudo-panel estimation rather than 9% as in the ordinary least-squares (OLS) estimation. This indicates that not controlling for unobservables such as ability and motivation biases the OLS estimation of returns upwards by about 4% on average, driven mainly by what happens in urban areas. It also suggests that males with higher ability seem to be acquiring more years of education. This is contrary to what has been observed recently in countries such as Thailand [Warunsiri, S., and R. McNown. 2010. “The Return to Education in Thailand: A Pseudo-Panel Approach.” World Development 38 (1): 1616–1625], where the opportunity cost of education seems to be high, such that high-ability individuals leave education for the labour market.